2009
DOI: 10.1037/a0014866
|View full text |Cite
|
Sign up to set email alerts
|

Emotion processing in the criminal psychopath: The role of attention in emotion-facilitated memory.

Abstract: The response modulation hypothesis specifies that low-anxious psychopathic individuals have difficulty processing information outside of their primary attentional focus. To evaluate the applicability of this model to affective processing, 239 offenders, classified using the Psychopathy Checklist-Revised (Hare, 2003) and the Welsh Anxiety Scale (Welsh, 1956), performed one of three emotion memory tasks that examined the effects of emotion on memory for primary and contextual information. Regardless of anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 30 publications
(40 reference statements)
0
33
0
2
Order By: Relevance
“…These findings suggest that psychopathic traits may not impair memory for emotional stimuli. While this contradicts existing research (e.g., Christianson et al 1996), it is possible that psychopathic traits are more relevant to attentional factors (see Glass and Newman 2009). Recent studies have argued that impairments on emotional tasks likely result from attentional deficits and not from amygdala-mediated emotional dysregulation (Newman et al 2010).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…These findings suggest that psychopathic traits may not impair memory for emotional stimuli. While this contradicts existing research (e.g., Christianson et al 1996), it is possible that psychopathic traits are more relevant to attentional factors (see Glass and Newman 2009). Recent studies have argued that impairments on emotional tasks likely result from attentional deficits and not from amygdala-mediated emotional dysregulation (Newman et al 2010).…”
Section: Discussionmentioning
confidence: 80%
“…Zhu and colleagues (2010) reported that individuals with characteristics reflective of psychopathy (although not directly assessed) were more susceptible to false recall due to the presence of misinformation. Previous studies suggest that if persons high in psychopathic traits demonstrate an emotional memory bias and impaired peripheral recollection (see Glass and Newman 2009;Zhu et al 2010), then they may be susceptible to misinformation similar to (or more so than) persons low in these traits. If, however, psychopathic traits are related to equivalent or unimpaired recall of central and peripheral details (see Christianson et al 1996), individuals possessing psychopathic traits should be less influenced by the presentation of misleading information (as they would be equally attending to both central and peripheral information in a scene).…”
Section: Psychopathic Traits Emotion and Memorymentioning
confidence: 97%
See 1 more Smart Citation
“…[36][37][38][39] Because no published studies have examined hemodynamic activity in such situations, it is plausible that these situations will yield evidence of functional anomalies common to successful and unsuccessful psychopathy. Alternatively, if successful psychopathy represents a syndrome largely distinct from unsuccessful psychopathy, successful psychopaths may not exhibit these state-dependent cognitive deficits.…”
Section: 34mentioning
confidence: 99%
“…difficulties in evaluating emotion (Cleckley, 1976) and in responding appropriately to these (Lorenz & Newman, 2002) and 4.) difficulties in attending to emotion correctly (Glass & Newman, 2009;Baskin-Sommerset al, 2013).…”
mentioning
confidence: 99%